Fully exfoliated graphene oxide accelerates epoxy resin curing, and results in dramatic improvement of the polymer mechanical properties. (1st April 2019) - Surnova, Albina; Balkaev, Dinar; Musin, Delus; Amirov, Rustem; Dimiev, Ayrat M.
Abstract: In this study, we propose a new approach for the homogeneous liquid-phase transfer of graphene oxide (GO) into epoxy resin. This makes the process more efficient, while achieving fully uniform distribution of GO flakes within the epoxy matrix. Introduction of as little as 0.4% and 0.6% GO drastically increases the viscosity of the compositions, pointing at the highly exfoliated condition of GO in the resin. A significant accelerating effect of GO on the curing reaction is attributed to reactive groups on the GO surface. The study of the thermo-mechanical properties revealed that the introduction of relatively small amount of GO (0.2 wt%) into the epoxy matrix results in the increase of the storage modulus by 25.4% (3035 MPa) relative to the neat epoxy polymer (2420 MPa). The use of the high-temperature curing agent affords the composites with significantly higher glass transition temperatures, compared to the low-temperature curing agent, broadening the scope of their potential applications.